PENGGUNAAN PRINCIPAL COMPONENT ANALYSIS (PCA) DAN K-NEAREST NEIGHBORS (KNN) DALAM KLASIFIKASI SAYURAN MENTIMUN, PARE, DAN TERONG - Syarif, Ahmad; Ramadhanu, Agung (Smart Education, 2025)
Abstract: The classification of vegetable types is an important aspect of the agricultural industry to improve the efficiency of product management, packaging, and distribution. This study aims to implement the Principal Component Analysis (PCA) and K-Nearest Neighbors (KNN) methods in the vegetable classification process, especially for cucumbers, squash, and eggplants. PCA is used to reduce the data dimensions and extract the key significant features that distinguish vegetable categories. Meanwhile, KNN is applied as a classification algorithm based on the proximity of these key features. The research dataset consists of digital images of vegetables extracted into color, texture, and shape attributes. The results show that the combination of PCA and KNN is able to significantly improve the classification accuracy by minimizing computational complexity. Experiments are carried out with various numbers of main components in PCA and variations in kkk parameter values in KNN to determine the optimal configuration. In the best configuration, this method achieves a classification accuracy of 90%, with PCA effectively reducing the data dimension by 95% without losing important information. In conclusion, this approach has great potential to be implemented in vegetable classification automation systems to support efficiency in the agricultural supply chain. Keywords: Vegetables classification, Principal Component Analysis (PCA), K-Nearest Neighbors(KNN), cucumber, bitter melon, eggplant.Abstrak: Klasifikasi jenis sayuran merupakan salah satu aspek penting dalam industri pertanian untuk meningkatkan efisiensi pengelolaan produk, pengemasan, serta distribusi. Penelitian ini bertujuan untuk mengimplementasikan metode Principal Component Analysis (PCA) dan K-Nearest Neighbors (KNN) dalam proses klasifikasi sayuran, khususnya mentimun, pare, dan terong. PCA digunakan untuk mengurangi dimensi data dan mengekstraksi fitur utama yang signifikan dalam membedakan kategori sayuran. Sementara itu, KNN diterapkan sebagai algoritma klasifikasi berdasarkan kedekatan fitur-fitur utama tersebut. Dataset penelitian terdiri atas citra digital sayuran yang diekstraksi menjadi atribut warna, tekstur, dan bentuk. Hasil penelitian menunjukkan bahwa kombinasi PCA dan KNN mampu meningkatkan akurasi klasifikasi secara signifikan dengan meminimalkan kompleksitas komputasi. Eksperimen dilakukan dengan berbagai jumlah komponen utama pada PCA dan variasi nilai parameter kkk pada KNN untuk menentukan konfigurasi optimal. Pada konfigurasi terbaik, metode ini mencapai akurasi klasifikasi sebesar 90%, dengan PCA secara efektif mereduksi dimensi data hingga 95% tanpa kehilangan informasi penting. Kesimpulannya, pendekatan ini memiliki potensi yang besar untuk diimplementasikan dalam sistem otomatisasi klasifikasi sayuran guna mendukung efisiensi dalam rantai pasok agrikultur. Kata kunci: Klasifikasi sayuran, Principal Component Analysis (PCA), K-Nearest Neighbors (KNN), mentimun, pare, terong.